Functional deltoid muscle reconstruction following an extensive squamous cell carcinoma resection - Tang, Weng Jun; Mat Saad, Arman Zaharil (PiscoMed Publishing, 2016)
Squamous cell carcinoma frequently occurs in an individual with albinism. In this case, the growth of the squamous cell carcinoma was aggressive that it invaded the deltoid muscle. After an oncologic resection, there was a huge defect which required near total resection of the deltoid muscle. Loss of deltoid muscle will lead to the loss of abduction and anterior flexion at the shoulder. This could be debilitating in a person’s normal daily life and activities. Restoration of the shoulder abduction and flexion function with a pedicle bipolar latissimus dorsi flap transfer was chosen in this case due to the versatility and reliability of the flap.